1991
DOI: 10.1002/eji.1830211002
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterial heat‐shock proteins as carrier molecules

Abstract: We have previously shown that the priming of mice with live Mycobacterium tuberculosis var. bovis (Bacillus Calmette-Guérin, BCG) and immunization with the repetitive malaria synthetic peptide (NANP)40 conjugated to purified protein derivative (PPD), led to the induction of high and long-lasting titers of anti-peptide IgG antibodies, overcoming the requirement of adjuvants and the genetic restriction of the antibody response to the peptide (Lussow et al., Proc. Natl. Acad. Sci. USA 1990. 87:2960). This initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
40
0
2

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 39 publications
4
40
0
2
Order By: Relevance
“…These resulls extend our previous results obtained in mice [9][10][11] and clearly show that such a vaccination strategy tnay be applicable lo higher animals, and possibly man. It is also interesting to note thai in the present series of experiments monkeys always received BCG and tbe immunogen subcutaneously (rather than intraperitoneally.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…These resulls extend our previous results obtained in mice [9][10][11] and clearly show that such a vaccination strategy tnay be applicable lo higher animals, and possibly man. It is also interesting to note thai in the present series of experiments monkeys always received BCG and tbe immunogen subcutaneously (rather than intraperitoneally.…”
Section: Discussionsupporting
confidence: 87%
“…Previous results from our laboratories have shown that the carrier elTect of PPD can, at least partially, be ascribed to myeobacterial heat shock proteins of 65 and 70 kD [10,11], and that previous priming with live BCG was required for the carrier effect of the hspR65, bul not (or (he carrier effect of the hspR70 [11]. To determine whether or not the same would apply to monkeys, groups of 2 4 .Vfl/m/n monkeys, primed or not primed with BCG, were immunized subculaneously with hspR65-or hspR70-(NANP)4(i conjugates in the absence of adjuvants.…”
Section: Carrier Effect Of Myeobacterial Hsp In Lhe Absence Of Adjuvantsmentioning
confidence: 91%
See 1 more Smart Citation
“…This is supported by a previous report that inhibition of another HSP (HSP90) abrogated inflammasome formation (34). It is noteworthy that there is a great deal of evidence that exogenous HSP70 acts as an adjuvant (35)(36)(37)(38), which has been marred by criticism that the HSP70 used may have been contaminated with LPS, flaggelin, or nucleotides (39). This critique cannot be applied to the present work as exogenous HSP70 has not been used, but endogenous, inducible HSP70 was up-regulated by alum.…”
Section: Discussionsupporting
confidence: 69%
“…They could mediate the T cell sensitization required for the production of antibodies and can be used in the development of vaccine(s) against TB (Lussow et al, 1991). Inside the host, T cells are involved in activating macrophages and controlling the mycobacterial infection.…”
Section: Hsps In Vaccine Development Against Tbmentioning
confidence: 99%